A Analisis Implementasi Kebijakan PLUT dalam Pengembangan UMKM - Muhammad roid, Muhammad roid; Habibur Rohman; Angguliyah Rizqi Amaliyah (Jurnal Mutiara Ilmu Akuntansi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy by contributing significantly to GDP and absorbing a large share of the workforce. However, MSMEs continue to face major challenges, including limited business legality, low human resource (HR) capacity, and difficulties in obtaining halal certification. To address these issues, the government established the Integrated Business Service Center (PLUT) as a consultation, assistance, and facilitation hub for MSME development. This study aims to analyze the implementation of the PLUT policy in supporting MSMEs, focusing on the issuance of Business Identification Numbers (NIB), capacity building for human resources, and facilitation of halal certification. A qualitative descriptive method was employed, with data collected through observations, in-depth interviews, and documentation. Data were analyzed using Miles & Huberman’s interactive model and Edwards III’s framework, which emphasizes communication, resources, disposition, and bureaucratic structure. The findings reveal that PLUT plays a crucial role in helping MSMEs secure business legality, providing training and managerial assistance, and supporting the halal certification process. Nevertheless, challenges remain, such as the limited number of consultants, bureaucratic complexity, and unequal access to digital infrastructure, which hinder the overall effectiveness of the services. The implications of this study highlight the need to strengthen PLUT’s capacity by recruiting more professional consultants, digitalizing services, and integrating with the OSS and BPJPH systems. These steps are expected to enhance the effectiveness and sustainability of PLUT’s implementation, thereby improving the competitiveness of MSMEs in the era of digital transformation.